The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3748/wjg.v27.i18.2122
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging-based artificial intelligence model in rectal cancer

Abstract: Rectal magnetic resonance imaging (MRI) is the preferred method for the diagnosis of rectal cancer as recommended by the guidelines. Rectal MRI can accurately evaluate the tumor location, tumor stage, invasion depth, extramural vascular invasion, and circumferential resection margin. We summarize the progress of research on the use of artificial intelligence (AI) in rectal cancer in recent years. AI, represented by machine learning, is being increasingly used in the medical field. The application of AI models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
(39 reference statements)
0
16
0
1
Order By: Relevance
“…We hypothesize that further studies, on a larger cohort of patients, could include several panels of clinical and paraclinical parameters in several machine learning algorithms or convolutional neural networks in order to better establish their predictive performance. These approaches allow better image segmentation or feature discrimination, and allow the analysis of a large dataset, even with high rates of missing data [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that further studies, on a larger cohort of patients, could include several panels of clinical and paraclinical parameters in several machine learning algorithms or convolutional neural networks in order to better establish their predictive performance. These approaches allow better image segmentation or feature discrimination, and allow the analysis of a large dataset, even with high rates of missing data [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of radiomics in CRC has shown great promise in advancing cancer diagnosis, treatment, and prognosis [26]. By extracting and analyzing a multitude of quantitative imaging features from medical images, radiomics provides valuable insights into tumor characteristics and behavior [40]. In this discussion, we will explore the key findings and implications of the reviewed literature on the applications of radiomics in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Wang, Deng, and Wu [23] CNN ML models can also use magnetic resonance imaging (MRI) results as inputs. This has been proved effective in predicting the responses of various patients towards chemotherapy with an accuracy rate of 95%.…”
Section: Luo Et Al [22] MLmentioning
confidence: 99%
“…Similarly, research spearheaded by Wang, Deng, and Wu [23] found that ML models that utilize magnetic resonance imaging (MRI) have proved effective in predicting the responses of various patients to chemotherapy, in addition to the evaluation of patient prognosis. The authors' focus was patients with rectal cancer, and the algorithm yielded an accuracy rate of 95% [23].…”
Section: Advantages and Limitations Of ML In Colorectal Surgerymentioning
confidence: 99%